OPTIMALISASI TANDA PERINGATAN (WARNING SIGN) TERHADAP PENINGKATAN PELAYANAN DI TERMINAL BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Rangga Satria Wardana; Lusiana Dewi Kusumayati; Moch Rifa'i (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Jenderal Ahmad Yani International Airport Semarang has complete facilities provided by PT. Angkasa Pura I (Persero). These facilities are in the form of signs or directions (signage), namely exits, check-in counters, departure, arrival, transit, toilets, warning signs, etc. Warning signs are placed in public areas such as terminals, domestic & international areas. However, at General Ahmad Yani's International Airport terminal, the placement of a warning sign is still not optimal. The topic of this research is the placement of a warning sign to improve service and safety for passengers, service users & officers. The purpose of this research is to make the movement easier, more directed and reach the destination safely. This study uses a qualitative descriptive method in the form of analyzing, describing and summarizing various conditions situation from various data collected in the form of interviews or observations regarding the problem under study that occurred in the field. The results showed that there were still signs in the terminal of Jendral Ahmad Yani Semarang International Airport that did not comply with the standards stated in KM No.22 of 200, which should have been easy to see and understand and understand. Efforts to optimize the placement of signs at the terminal can be carried out by the operation party by reviewing the location in terms of the building structure and space for movement and evaluating any criticism, suggestions, and questions from service users.